Double-sided adhesive tape

JP7652707B2Active Publication Date: 2025-03-27SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021559569
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-03-12
Publication Date
2025-03-27
Estimated Expiration
2041-03-12

AI Technical Summary

Benefits of technology

【0078】 本発明によれば、傾き荷重に対する耐性に優れ、両粘着面におけるリワーク性に優れた両面粘着テープを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652707000004
    Figure 0007652707000004
  • Figure 0007652707000005
    Figure 0007652707000005
  • Figure 0007652707000006
    Figure 0007652707000006
Patent Text Reader

Abstract

The purpose of the present invention is to provide a double-sided adhesive tape that has excellent resistance to an inclined load and excellent reworkability of both adhesive surfaces. The present invention is a double-sided adhesive tape comprising a foam base material, and a first adhesive layer and a second adhesive layer that are respectively provided to the two surfaces of the foam base material, wherein the foam base material has a shear fracture strength of at least 200 N / inch2, and a first resin layer and a second resin layer, which each have a tensile elastic modulus of at least 5.0 MPa, are respectively provided between the foam base material and the first adhesive layer and between the foam base material and the second adhesive layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a double-sided pressure-sensitive adhesive tape that has excellent resistance to tilted loads and excellent reworkability on both adhesive surfaces. [Background technology]

[0002] Adhesive tapes are widely used for fixing electronic components. Specifically, for example, adhesive tapes are used for fixing the front cover panel to the housing of a display device such as a television or a monitor. Such adhesive tapes are used in a shape such as a picture frame and are arranged around the periphery of the display screen.

[0003] In recent years, as a result of the pursuit of design and functionality, the frames of display devices such as televisions and monitors have become narrower, and expectations for bezel-less display devices are also increasing. In the conventional manufacturing of display devices, the cover panel was sometimes fixed to the housing by fitting or screwing, but since fitting or screwing is difficult for display devices with narrower frames, there is an increasing demand for fixing with adhesive tape, and adhesive tapes are also becoming thinner and narrower.

[0004] As an example of an adhesive tape that can be used in such a display device, Patent Documents 1 and 2 describe an impact absorbing tape in which an acrylic adhesive layer is integrally laminated on at least one surface of a base layer, and the base layer is a cross-linked polyolefin resin foam sheet having a specific degree of cross-linking and aspect ratio of bubbles. Since a foam substrate has appropriate flexibility and can relieve stress, using a foam substrate as the substrate for an adhesive tape has advantages such as improved impact resistance and reduced display unevenness that occurs on a display device. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-242541 A [Patent Document 2] JP 2009-258274 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, display devices such as televisions and monitors are becoming larger, and the weight of fixed members such as cover panels and housings is also increasing. For this reason, adhesive tapes, especially adhesive tapes that have become thinner and narrower, are subjected to much larger loads than before, and are required to have better load resistance than before. In particular, in applications such as wall-mounted televisions, the display devices are increasingly being installed in a state tilted forward, for example, by about 20° from the vertical direction, and are required to have better resistance to tilt loads.

[0007] In addition, in recent years, electronic components have tended to become expensive, and so there is a demand for components to be reworkable, for example, when a defect occurs during component fixing. One method for reworking components is, for example, to tear the foam base material of the adhesive tape with a cutter blade, break the layers, remove the component, and peel off the part of the adhesive tape remaining on the component. In such cases, the adhesive tape is required to have excellent reworkability that allows it to be peeled off and removed without leaving any residue on the component. In particular, double-sided adhesive tapes are required to have reworkability on both adhesive surfaces.

[0008] An object of the present invention is to provide a double-sided pressure-sensitive adhesive tape that has excellent resistance to tilting loads and excellent reworkability on both adhesive surfaces. [Means for solving the problem]

[0009] The present invention relates to a double-sided pressure-sensitive adhesive tape having a foam substrate and a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer on each side of the foam substrate, the foam substrate having a shear breaking strength of 200 N / inch 2The double-sided pressure-sensitive adhesive tape has a first resin layer and a second resin layer, each having a tensile modulus of elasticity of 5.0 MPa or more, between the foam substrate and the first pressure-sensitive adhesive layer, and between the foam substrate and the second pressure-sensitive adhesive layer. The present invention will be described in detail below.

[0010] The present inventors have investigated adjusting the shear breaking strength of a foam substrate in a double-sided pressure-sensitive adhesive tape having a foam substrate and a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer on each side of the foam substrate. The present inventors have found that by adjusting the shear breaking strength of the foam substrate within a specific range, it is possible to increase the strength of the foam substrate while employing a foam substrate that has appropriate flexibility and can exhibit excellent stress relaxation properties, thereby obtaining a double-sided pressure-sensitive adhesive tape with excellent resistance to tilting loads. The present inventors also found that the rigidity of the double-sided adhesive tape affects the resistance to tilt load. Therefore, the present inventors further arranged a first resin layer and a second resin layer, the tensile modulus of which is adjusted to a specific range, between the foam substrate and the first adhesive layer, and between the foam substrate and the second adhesive layer. The present inventors found that by arranging such a first resin layer and a second resin layer, these resin layers have appropriate rigidity, and therefore excellent reworkability can be imparted to both adhesive surfaces, and the deformation stress of the foam substrate caused by the application of a tilt load can be alleviated and made difficult to be transmitted to the adhesive layer, thereby further improving the resistance to tilt load. This led to the completion of the present invention.

[0011] Fig. 1 is a cross-sectional view showing a schematic diagram of one example of the double-sided pressure-sensitive adhesive tape of the present invention. The double-sided pressure-sensitive adhesive tape 1 shown in Fig. 1 has a first pressure-sensitive adhesive layer 31 and a second pressure-sensitive adhesive layer 32 on both sides of a foam substrate 2. A first resin layer 41 is disposed between the foam substrate 2 and the first pressure-sensitive adhesive layer 31, and a second resin layer 42 is disposed between the foam substrate 2 and the second pressure-sensitive adhesive layer 32.

[0012] The double-sided pressure-sensitive adhesive tape of the present invention has a foam substrate and a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer on each side of the foam substrate. By having the foam substrate, the double-sided pressure-sensitive adhesive tape of the present invention can exhibit excellent stress relaxation properties. The foam substrate may have an open cell structure or a closed cell structure, but preferably has a closed cell structure. The closed cell structure makes it easier to adjust the shear breaking strength of the foam substrate to a range described below. As a result, deformation and interlaminar breakage of the foam substrate when a tilting load is applied can be suppressed, and the resistance of the double-sided pressure-sensitive adhesive tape to a tilting load is improved.

[0013] The foam substrate may have a single layer structure or a multi-layer structure. The foam substrate is not particularly limited, and examples thereof include polyurethane foam, polyolefin foam, rubber-based resin foam, acrylic foam, etc. Among them, polyurethane foam or polyolefin foam is preferred because it can exhibit excellent stress relaxation. Polyolefin foam is more preferred because it has moderate flexibility and can exhibit excellent stress relaxation, and the shear rupture strength is higher, improving the resistance of the double-sided adhesive tape to an inclined load. In addition, polyolefin foam having a closed cell structure is more preferred because it further improves the resistance of the double-sided adhesive tape to an inclined load.

[0014] The polyurethane foam is not particularly limited, and examples thereof include polyurethane foams made of a urethane resin composition containing a polyisocyanate and a polyol. Such polyurethane foams can be produced by heat curing the urethane resin composition.

[0015] The polyolefin foam is not particularly limited, and examples thereof include foams made of resins such as polyethylene-based resins, polypropylene-based resins, polybutadiene-based resins, etc. Among these, foams made of polyethylene-based resins are preferred because they can easily produce flexible polyolefin foams and exhibit excellent stress relaxation properties, and because they have higher shear rupture strength and improve the resistance of the double-sided pressure-sensitive adhesive tape to an inclined load.

[0016] The foam base material has a lower limit of shear breaking strength of 200 N / inch 2 It is. The shear breaking strength is 200N / inch 2 If the shear breaking strength is equal to or greater than this, the strength of the foam substrate is sufficiently high, and deformation and interlaminar breakage of the foam substrate when an inclined load is applied can be suppressed, and the resistance of the double-sided pressure-sensitive adhesive tape to an inclined load can be improved. 2 , and a more preferable lower limit is 300N / inch 2 , and a more preferable lower limit is 400N / inch 2 The upper limit of the shear breaking strength is not particularly limited, but a preferable upper limit is 700 N / inch 2 The shear breaking strength is 700N / inch 2 If the shear breaking strength is equal to or less than 600 N / inch, the strength of the foam substrate can be prevented from becoming too high, and the stress relaxation property of the double-sided pressure-sensitive adhesive tape can be improved. 2 It is.

[0017] The shear breaking strength can be measured by the following method. FIG. 2 shows a schematic diagram of a method for measuring the shear breaking strength. First, a test piece 18 of double-sided adhesive tape with a size of 25 mm×25 mm and two SUS plates 19 with a size of 125 mm×50 mm and a thickness of 2 mm are laminated as shown in FIG. 2. This laminate is pressed with a weight of 5 kg for 10 seconds, and then left to stand for 24 hours to prepare a test sample in which two SUS plates 19 are bonded together via the test piece 18. After fixing one SUS plate 19 of this test sample, the upper one of the other SUS plate 19 is pulled at 23° C. in a direction perpendicular to the lamination direction of the SUS plates (in the direction of the arrow in the figure) at 12.7 mm / min, and the force (breaking strength) applied to the test piece 18 when the test piece 18 breaks is measured. Note that the breakage of the test piece 18 means that the foam base material breaks between layers.

[0018] The shear breaking strength of the foam substrate can be adjusted, for example, by increasing the density of the foam substrate, increasing the proportion of monomers constituting the foam substrate that have a high glass transition temperature (Tg) and a large molecular weight when made into a homopolymer, or increasing the degree of crosslinking of the foam substrate.

[0019] The density of the foam substrate is not particularly limited, but the preferred lower limit is 0.03 g / cm 3 , the preferred upper limit is 0.8 g / cm 3 By setting the density of the foam substrate within this range, the double-sided pressure-sensitive adhesive tape can exhibit excellent resistance to tilted load and excellent stress relaxation properties. From the viewpoint of further improving the resistance to tilted load and stress relaxation properties of the double-sided pressure-sensitive adhesive tape, a more preferable lower limit of the density of the foam substrate is 0.04 g / cm 3 , and a more preferable upper limit is 0.7 g / cm 3 and a more preferable lower limit is 0.05 g / cm 3 , and a more preferable upper limit is 0.6 g / cm 3 A particularly preferred lower limit of the density of the foam substrate is 0.06 g / cm 3 , and a particularly preferred upper limit is 0.5 g / cm 3 It is. The density can be measured using an electronic specific gravity meter (for example, "ED120T" manufactured by Mirage) in accordance with JIS K 6767.

[0020] The glass transition temperature (Tg) of the homopolymer of the monomer constituting the foam substrate is not particularly limited, but a preferred lower limit is −30° C. and a preferred upper limit is 10° C. By setting the glass transition temperature (Tg) of the homopolymer of the monomer constituting the foam substrate within this range, the double-sided pressure-sensitive adhesive tape can exhibit excellent resistance to an inclined load and excellent stress relaxation properties.

[0021] The 25% compressive strength of the foam substrate is not particularly limited, but a preferred lower limit is 1 kPa, and a preferred upper limit is 100 kPa. By setting the 25% compressive strength of the foam substrate within this range, the double-sided pressure-sensitive adhesive tape can exhibit excellent resistance to tilted load and excellent stress relaxation properties. From the viewpoint of further improving the resistance to tilted load and stress relaxation properties of the double-sided pressure-sensitive adhesive tape, a more preferred lower limit of the 25% compressive strength of the substrate is 3 kPa, a more preferred upper limit is 80 kPa, an even more preferred lower limit is 5 kPa, and an even more preferred upper limit is 70 kPa. The 25% compressive strength can be determined in accordance with JIS K 6254:2016 by measuring as follows. The foam base material is cut to 20 mm x 20 mm to prepare a sample with a thickness of approximately 5 mm x 20 mm x 20 mm. The sample is compressed in the compression direction at a speed of 10 mm / min, and the pressure (N) at the point of 25% compression is confirmed. The 25% compression strength is calculated from the obtained pressure using the following formula (2). Note that the thickness of the sample is taken as 100, and the point at which the sample is compressed by 25% (the thickness of the sample is 75) is considered to be 25% compressed. Compressive strength (kPa) = pressure (N) / 0.4 (2)

[0022] The shear storage modulus of the foam base material is not particularly limited, but is preferably a value of 1.0×10 in a master curve synthesized at a reference temperature of 23° C. using a dynamic viscoelasticity device. -4~1.0×10 -5 The maximum shear storage modulus in the Hz range is 1.0×10 5 The frequency range corresponds to the low-speed peel stress that occurs when a restoring force or a repulsive force is applied to the double-sided adhesive tape. The maximum shear storage modulus in the frequency range is preferably 1.0×10 5 If the foam base material has a compressive strength of 100 Pa or less, the stress generated when a restoring force or a repulsive force is applied to the double-sided adhesive tape can be alleviated by the foam base material, making it difficult for the stress to be transmitted to the adhesive layer, thereby improving the stress relaxation properties of the double-sided adhesive tape. The shear storage modulus can be measured in the range of -60°C to 250°C at a heating rate of 5°C / min using a dynamic viscoelasticity measuring device (e.g., DVA-200 manufactured by IT Measurement Co., Ltd.). When measuring the shear storage modulus, in order to prevent the sample from shifting during the measurement, an adhesive is applied to both sides of the foam substrate and the measurement is performed. Such an adhesive is not particularly limited, but the thickness of the adhesive applied to both sides of the foam substrate is adjusted to 15% or less of the thickness of the foam substrate and the measurement is performed. By setting the thickness of the adhesive to 15% or less of the thickness of the foam substrate, the influence of the adhesive can be eliminated as much as possible and the shear storage modulus of the foam substrate can be measured.

[0023] The thickness of the foam substrate is not particularly limited, but the preferred lower limit is 100 μm, and the preferred upper limit is 1500 μm. If the thickness of the foam substrate is 100 μm or more, the foam substrate can be easily torn when torn with, for example, a cutter blade during rework. If the thickness of the foam substrate is 1500 μm or less, the deformation of the foam substrate when a tilting load is applied can be suppressed, and the resistance of the double-sided adhesive tape to a tilting load is improved. The more preferred lower limit of the thickness of the foam substrate is 150 μm, the more preferred upper limit is 1300 μm, the even more preferred lower limit is 250 μm, the even more preferred upper limit is 1200 μm, the even more preferred lower limit is 300 μm, and the even more preferred upper limit is 900 μm.

[0024] The first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer (hereinafter, both may be simply referred to as "pressure-sensitive adhesive layers") may have the same composition, or may have different compositions. The pressure-sensitive adhesive layer is not particularly limited, and examples thereof include an acrylic pressure-sensitive adhesive layer, a rubber-based pressure-sensitive adhesive layer, a urethane pressure-sensitive adhesive layer, a silicone-based pressure-sensitive adhesive layer, and the like. Among these, an acrylic pressure-sensitive adhesive layer containing an acrylic copolymer and a tackifier resin is preferred, since it is relatively stable against light, heat, moisture, and the like, and can adhere to various adherends (low adherend selectivity). In this case, both the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer may contain an acrylic copolymer and a tackifier resin, but it is sufficient that at least one selected from the group consisting of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer contains an acrylic copolymer and a tackifier resin.

[0025] The acrylic copolymer contained in the pressure-sensitive adhesive layer is preferably obtained by copolymerizing a monomer mixture containing butyl acrylate and / or 2-ethylhexyl acrylate, from the viewpoint of improving initial tack and thus improving ease of application at low temperatures.The acrylic copolymer is more preferably obtained by copolymerizing a monomer mixture containing butyl acrylate and 2-ethylhexyl acrylate. The preferred lower limit of the content of the butyl acrylate in the total monomer mixture is 40% by weight, and the preferred upper limit is 80% by weight. By keeping the content of the butyl acrylate within this range, it is possible to achieve both high adhesive strength and tackiness. The content of the 2-ethylhexyl acrylate in the total monomer mixture is preferably 10% by weight at the lower limit, 100% by weight at the upper limit, 30% by weight at the more preferred lower limit, 80% by weight at the more preferred upper limit, 50% by weight at the still more preferred upper limit, 60% by weight at the more preferred upper limit. By keeping the content of the 2-ethylhexyl acrylate within this range, high adhesive strength can be exhibited.

[0026] The monomer mixture may contain other copolymerizable polymerizable monomers other than butyl acrylate and 2-ethylhexyl acrylate as necessary. Examples of the other copolymerizable polymerizable monomers include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 3 carbon atoms, (meth)acrylic acid alkyl esters having an alkyl group with 13 to 18 carbon atoms, and functional monomers. Examples of the (meth)acrylic acid alkyl esters having an alkyl group with 1 to 3 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, etc. Examples of the (meth)acrylic acid alkyl esters having an alkyl group with 13 to 18 carbon atoms include tridecyl methacrylate, stearyl (meth)acrylate, etc. Examples of the functional monomers include hydroxyalkyl (meth)acrylate, glycerin dimethacrylate, glycidyl (meth)acrylate, 2-methacryloyloxyethyl isocyanate, (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, fumaric acid, etc. Among these, from the viewpoint of increasing the bulk strength and elastic modulus at high temperatures of the pressure-sensitive adhesive layer, hydroxyl-containing monomers such as hydroxyalkyl (meth)acrylate and glycerin dimethacrylate are preferred. That is, the acrylic copolymer preferably has a constituent unit derived from a hydroxyl-containing monomer.

[0027] To obtain the acrylic copolymer by copolymerizing the monomer mixture, the monomer mixture may be subjected to a radical reaction in the presence of a polymerization initiator. As a method for radically reacting the monomer mixture, i.e., a polymerization method, a conventionally known method may be used, such as solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc.

[0028] The weight average molecular weight (Mw) of the acrylic copolymer is preferably 300,000 at the lower limit and 2,000,000 at the upper limit. If the weight average molecular weight of the acrylic copolymer is 300,000 or more, the bulk strength and elastic modulus at high temperatures of the pressure-sensitive adhesive layer are increased, and the pressure-sensitive adhesive layer can be prevented from cohesively breaking when an inclined load is applied, and the resistance of the double-sided pressure-sensitive adhesive tape to an inclined load is improved. If the weight average molecular weight of the acrylic copolymer is 2,000,000 or less, the pressure-sensitive adhesive layer has excellent interface wettability, and therefore, the pressure-sensitive adhesive layer can be prevented from peeling at the interface when an inclined load is applied, and the resistance of the double-sided pressure-sensitive adhesive tape to an inclined load is improved. The more preferred lower limit of the weight average molecular weight is 400,000, and the more preferred upper limit is 1,900,000, and the even more preferred lower limit is 500,000, and the even more preferred upper limit is 1,800,000, and the even more preferred lower limit is 600,000, and the even more preferred upper limit is 1,750,000. The weight average molecular weight (Mw) is the weight average molecular weight calculated using standard polystyrene standards by GPC (gel permeation chromatography). The detailed measurement method of GPC is as follows. The acrylic copolymer-containing solution is diluted 50 times with tetrahydrofuran (THF) and the resulting diluted solution is filtered through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). The resulting filtrate is fed to a gel permeation chromatograph (Waters, 2690 Separations Model) and subjected to GPC measurement under conditions of a sample flow rate of 1 milliliter / min and a column temperature of 40°C, and the polystyrene-equivalent molecular weight of the acrylic copolymer is measured to determine the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn). A GPC KF-806L (Showa Denko) can be used as the column, and a differential refractometer can be used as the detector.

[0029] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the acrylic copolymer is preferably 1.05 at the lower limit and 5.0 at the upper limit. When Mw / Mn is 5.0 or less, the proportion of low molecular weight components is suppressed, the elastic modulus of the pressure-sensitive adhesive layer at high temperatures is increased, and the pressure-sensitive adhesive layer is prevented from undergoing cohesive failure when subjected to an inclined load, improving the resistance of the double-sided pressure-sensitive adhesive tape to an inclined load. The more preferred upper limit of Mw / Mn is 4.5, the even more preferred upper limit is 4, and the even more preferred upper limit is 3.5.

[0030] Examples of the tackifier resin contained in the pressure-sensitive adhesive layer include rosin resins, rosin ester resins, hydrogenated rosin resins, terpene resins, terpene phenol resins, coumarone-indene resins, alicyclic saturated hydrocarbon resins, C5 petroleum resins, C9 petroleum resins, and C5-C9 copolymer petroleum resins. These tackifier resins may be used alone or in combination of two or more. Among them, rosin resins or terpene resins are preferred, and rosin resins or terpene resins having a hydroxyl group are more preferred.

[0031] The tackifier resin has a softening temperature of preferably 70°C at the lower limit and 170°C at the upper limit. If the softening temperature is 70°C or higher, the pressure-sensitive adhesive layer can be prevented from becoming too soft, which can prevent the resistance to tilting load from decreasing. If the softening temperature is 170°C or lower, the pressure-sensitive adhesive layer has excellent interface wettability, which can prevent interface peeling when a tilting load is applied, thereby improving the resistance of the double-sided pressure-sensitive adhesive tape to a tilting load. A more preferable lower limit of the softening temperature is 120°C. The softening temperature is a softening temperature measured by the ring and ball method according to JIS K2207.

[0032] The tackifier resin has a hydroxyl value of preferably 25 at the lower limit and 200 at the upper limit. With a hydroxyl value within the above range, the pressure-sensitive adhesive layer has excellent interface wettability, and therefore can suppress interface peeling when a tilted load is applied, improving the resistance of the double-sided pressure-sensitive adhesive tape to tilted loads. The more preferred lower limit of the hydroxyl value is 30, and the more preferred upper limit is 160. The hydroxyl value can be measured according to JIS K1557 (phthalic anhydride method).

[0033] The content of the tackifier resin is not particularly limited, but the preferred lower limit is 10 parts by weight and the preferred upper limit is 60 parts by weight relative to 100 parts by weight of the acrylic copolymer. If the content of the tackifier resin is 10 parts by weight or more, the adhesive strength of the pressure-sensitive adhesive layer is high. If the content of the tackifier resin is 60 parts by weight or less, the pressure-sensitive adhesive layer can be prevented from becoming too hard and losing its adhesive strength.

[0034] The pressure-sensitive adhesive layer preferably has a crosslinked structure formed between the main chains of the resins (e.g., the acrylic copolymer, the tackifier resin, etc.) constituting the pressure-sensitive adhesive layer by adding a crosslinking agent. By adjusting the type and amount of the crosslinking agent, the gel fraction of the pressure-sensitive adhesive layer can be easily adjusted. The crosslinking agent is not particularly limited, and examples thereof include isocyanate-based crosslinking agents, aziridine-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-type crosslinking agents, etc. Among these, isocyanate-based crosslinking agents are preferred. The amount of the crosslinking agent added is preferably 0.01 part by weight at its lower limit and 10 parts by weight at its upper limit, more preferably 0.1 part by weight at its lower limit and 6 parts by weight at its upper limit, per 100 parts by weight of the acrylic copolymer.

[0035] The pressure-sensitive adhesive layer may contain a silane coupling agent for the purpose of improving adhesive strength. The silane coupling agent is not particularly limited, and examples thereof include epoxy silanes, acrylic silanes, methacrylic silanes, amino silanes, and isocyanate silanes.

[0036] The pressure-sensitive adhesive layer may contain a coloring material for the purpose of imparting light-shielding properties. The coloring material is not particularly limited, and examples thereof include carbon black, aniline black, titanium oxide, etc. Among these, carbon black is preferred because it is relatively inexpensive and chemically stable.

[0037] The pressure-sensitive adhesive layer may contain conventionally known fine particles and additives, such as inorganic fine particles, conductive fine particles, antioxidants, foaming agents, organic fillers, and inorganic fillers, as necessary.

[0038] The gel fraction of the pressure-sensitive adhesive layer is not particularly limited, but the preferred lower limit is 1% by weight, and the preferred upper limit is 80% by weight. If the gel fraction is 1% by weight or more, the bulk strength and elastic modulus at high temperatures of the pressure-sensitive adhesive layer are increased, and the pressure-sensitive adhesive layer can be prevented from cohesively breaking when a tilting load is applied, and the resistance of the double-sided pressure-sensitive adhesive tape to a tilting load is improved. If the gel fraction is 80% by weight or less, the pressure-sensitive adhesive layer has excellent interface wettability, and therefore the interface peeling can be prevented when a tilting load is applied, and the resistance of the double-sided pressure-sensitive adhesive tape to a tilting load is improved. The more preferred lower limit of the gel fraction is 10% by weight, and the more preferred upper limit is 75% by weight, and the even more preferred lower limit is 20% by weight, and the even more preferred upper limit is 70% by weight, and the even more preferred lower limit is 30% by weight, and the even more preferred upper limit is 65% by weight. The first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer may both have a gel fraction within the above range, but it is sufficient that the gel fraction of at least one selected from the group consisting of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer is within the above range. The gel fraction of the pressure-sensitive adhesive layer can be measured by the following method. For measuring the gel fraction, a double-sided adhesive tape having an adhesive layer but no resin layer is prepared, and the double-sided adhesive tape is cut into a flat rectangular shape of 50 mm x 100 mm to prepare a test piece. The test piece is immersed in ethyl acetate at 23°C for 24 hours, then removed from the ethyl acetate and dried at 110°C for 1 hour. The weight of the test piece after drying is measured, and the gel fraction is calculated using the following formula (1). Note that no release film is laminated on the test piece to protect the adhesive layer. Gel fraction (weight%) = 100 × (W2 - W0) / (W1 - W0) (1) (W0: weight of substrate, W1: weight of test piece before immersion, W2: weight of test piece after immersion and drying)

[0039] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but the preferred lower limit of the thickness of the pressure-sensitive adhesive layer on one side is 20 μm, and the preferred upper limit is 100 μm. If the thickness of the pressure-sensitive adhesive layer is 20 μm or more, the adhesive strength of the pressure-sensitive adhesive layer is sufficient. If the thickness of the pressure-sensitive adhesive layer is 100 μm or less, the stress relaxation property of the foam substrate can sufficiently contribute to the stress relaxation property of the double-sided pressure-sensitive adhesive tape as a whole. The more preferred lower limit of the thickness of the pressure-sensitive adhesive layer is 25 μm, and the more preferred upper limit is 80 μm, and the even more preferred lower limit is 30 μm, and the even more preferred upper limit is 70 μm, and the even more preferred lower limit is 35 μm, and the even more preferred upper limit is 65 μm. The thickness of the pressure-sensitive adhesive layer can be measured using a dial thickness meter (for example, "ABS Digimatic Indicator" manufactured by Mitutoyo Corporation).

[0040] The double-sided pressure-sensitive adhesive tape of the present invention has a first resin layer and a second resin layer, each having a tensile modulus of elasticity of 5.0 MPa or more, between the foam substrate and the first pressure-sensitive adhesive layer, and between the foam substrate and the second pressure-sensitive adhesive layer (hereinafter, both layers are simply referred to as "resin layers"). That is, the double-sided pressure-sensitive adhesive tape of the present invention has a first resin layer between the foam substrate and the first pressure-sensitive adhesive layer, and has a second resin layer between the foam substrate and the second pressure-sensitive adhesive layer. The first resin layer and the second resin layer may have the same composition, or may have different compositions. By having the above-mentioned resin layer, the double-sided pressure-sensitive adhesive tape of the present invention employs the above-mentioned foam substrate, which has appropriate flexibility and can exhibit excellent stress relaxation properties, yet can be peeled off and removed during rework without leaving any residue of the foam substrate on the adherend (for example, a portion of the foam substrate that has broken off and remains), thereby exhibiting excellent reworkability on both adhesive surfaces.

[0041] The resin layer has a tensile modulus of 5.0 MPa or more. If the resin layer has a tensile modulus of 5.0 MPa or more, it is possible to impart excellent reworkability to both adhesive surfaces, and to alleviate the deformation stress of the foam base material caused by the application of an inclined load, making it difficult to transmit the stress to the adhesive layer, thereby suppressing interfacial peeling of the adhesive layer. The preferred lower limit of the tensile modulus of the resin layer is 7 MPa, more preferred lower limit is 10 MPa, and even more preferred lower limit is 20 MPa. The first resin layer and the second resin layer both have a tensile modulus of 5.0 MPa or more. The upper limit of the tensile modulus of the resin layer is not particularly limited, but a preferred upper limit is 150 MPa. Usually, the pressure-sensitive adhesive tape is provided in a state of being wound in a roll, and is used by being pulled out from the roll. If the tensile modulus of the resin layer is 150 MPa or less, the flexibility of the entire double-sided pressure-sensitive adhesive tape is ensured, the double-sided pressure-sensitive adhesive tape can be easily wound into a roll, the handling property is significantly improved, and the occurrence of wrinkles and creases during winding can be suppressed. A more preferred upper limit of the tensile modulus of the resin layer is 100 MPa, a further more preferred upper limit is 80 MPa, and a further more preferred upper limit is 50 MPa. The first resin layer and the second resin layer may both have a tensile modulus of 150 MPa or less, but it is sufficient that at least one selected from the group consisting of the first resin layer and the second resin layer has a tensile modulus of 150 MPa or less. If the tensile modulus of both the first resin layer and the second resin layer is 150 MPa or less, the double-sided pressure-sensitive adhesive tape has particularly excellent flexibility.

[0042] The first resin layer and the second resin layer may have the same tensile modulus, but it is preferable that there is a difference in tensile modulus between the first resin layer and the second resin layer, and it is more preferable that the difference in tensile modulus between the first resin layer and the second resin layer is 20 MPa or more. If the difference in tensile modulus is 20 MPa or more, it is possible to more effectively prevent wrinkles and creases from occurring when the double-sided adhesive tape is wound into a roll. The lower limit of the difference in tensile modulus is more preferably 30 MPa, even more preferably 100 MPa, and even more preferably 500 MPa.

[0043] When the breaking stress of the resin layer is 6 MPa or more and less than 50 MPa, the breaking elongation of the resin layer is preferably 300% or more. That is, when the breaking stress is in a relatively low range of 6 MPa or more and less than 50 MPa, the breaking elongation of the resin layer is 300% or more, so that the double-sided adhesive tape can exhibit better reworkability. In this case, the breaking elongation of the resin layer is more preferably 400%, even more preferably 450%, and even more preferably 500%. In this case, the breaking elongation of the resin layer is not particularly limited in upper limit, but is substantially about 1500% in upper limit. When the breaking stress of the resin layer is 50 MPa or more, the breaking elongation is preferably 110% or more. Even when the breaking stress is in the relatively high range of 50 MPa or more, if the breaking elongation is 110% or more, the double-sided adhesive tape can exhibit better reworkability. In this case, the lower limit of the breaking elongation of the resin layer is more preferably 150%, and even more preferably 200%. In this case, the upper limit of the breaking elongation of the resin layer is not particularly limited, but is substantially about 1500%.

[0044] The breaking stress of the resin layer is not particularly limited, but from the viewpoint of improving reworkability, the lower limit is preferably 6 MPa, more preferably 11.5 MPa, and even more preferably 15 MPa. The upper limit of the breaking stress of the resin layer is not particularly limited, but is substantially about 200 MPa.

[0045] In this specification, the breaking stress, breaking elongation and tensile modulus refer to the mechanical properties of the resin layer, and can be measured by a method in accordance with JIS K 7161. Specifically, for example, a punching blade "Tension No. 1 Dumbbell Shape" manufactured by Kobunshi Keiki Co., Ltd. is used to punch the resin layer into a dumbbell shape to prepare a test piece. The obtained test piece is measured at a tensile speed of 100 mm / min in an environment of 23°C and 50% RH using, for example, an "Autograph AGS-X" manufactured by Shimadzu Corporation to break the test piece. The breaking stress is calculated from the breaking strength per unit area when the test piece breaks. The breaking elongation is calculated from the elongation when the test piece breaks by "(distance between grippers at break / initial distance between grippers) x 100". The tensile modulus is calculated from the slope of the tensile strength between 1% and 3% strain.

[0046] The resin constituting the resin layer is not particularly limited, and examples thereof include polyester resins such as polyethylene terephthalate, acrylic resins, polyethylene resins, polypropylene resins, polyvinyl chloride, epoxy resins, silicone resins, phenol resins, polyimide, polyester resins, polycarbonates, etc. Among these, acrylic resins, polyethylene resins, polypropylene resins, and polyester resins are preferred because the double-sided adhesive tape has excellent flexibility. Among polyester resins, polyethylene terephthalate is preferred.

[0047] In addition, the resin constituting the resin layer is preferably a thermoplastic elastomer from the viewpoint of further improving stress relaxation properties, reworkability, and roll winding properties. In particular, it is preferable that at least one selected from the group consisting of the first resin layer and the second resin layer contains a thermoplastic elastomer, and when there is a difference in tensile modulus between the first resin layer and the second resin layer, it is preferable that the resin layer having a lower tensile modulus contains a thermoplastic elastomer.

[0048] The thermoplastic elastomer may be a styrene-based (co)polymer, an olefin-based (co)polymer, a vinyl chloride-based (co)polymer, a polyether ester-based triblock (co)polymer, a polyester-based (co)polymer, a urethane-based (co)polymer, an amide-based (co)polymer, or an acrylic-based (co)polymer. Among them, the thermoplastic elastomer is preferably an acrylic (co)polymer, a styrene-based (co)polymer, or an olefin-based (co)polymer, from the viewpoint of being able to exhibit strength, elongation, flexibility, and self-adhesiveness as an elastic body, and being able to exhibit excellent reworkability while further improving the adhesion between the resin layer and the foam substrate. Furthermore, it is more preferable that the thermoplastic elastomer is an acrylic (co)polymer or a styrene-based (co)polymer, and even more preferable that the thermoplastic elastomer is a styrene-based (co)polymer.

[0049] From the viewpoint of further improving the resistance to tilt load and reworkability, the thermoplastic elastomer is preferably a block copolymer, and more preferably a block copolymer having a hard segment and a soft segment. The fact that the resin layer contains the block copolymer having the hard segment and the soft segment can be confirmed by observing one or more peaks above and below 23°C when differential scanning calorimetry (DSC) of the resin layer is performed.

[0050] The block copolymer preferably contains a triblock copolymer, and more preferably contains a triblock copolymer having a hard segment and a soft segment. By using such a triblock copolymer, the strength, elongation, flexibility, and self-adhesiveness of an elastic body can be exhibited, and the adhesion between the resin layer and the foam substrate can be further improved while exhibiting excellent reworkability.

[0051] Furthermore, from the viewpoint of further enhancing the resistance to tilted load and reworkability, it is also preferable that the block copolymer contains a diblock copolymer and a triblock copolymer, that is, the block copolymer is a mixture of a diblock copolymer and a triblock copolymer. The triblock ratio (content of triblock copolymer) in the block copolymer is preferably 50% by weight or more from the viewpoint of further improving the resistance to tilt load and reworkability. The triblock ratio is more preferably 55% by weight or more, and even more preferably 65% ​​by weight or more. The triblock ratio may be 100% by weight, and is usually 100% by weight or less. The triblock ratio in the block copolymer can be determined by GPC measurement. More specifically, after preparing a diblock copolymer and after preparing a mixture of a diblock copolymer and a triblock copolymer, GPC measurement is performed, and the triblock ratio can be determined from the difference in distribution obtained.

[0052] The ratio of the hard segment in the block copolymer is preferably 22% by weight or more and 50% by weight or less, more preferably 23% by weight or more and 45% by weight or less, even more preferably 24% by weight or more and 40% by weight or less, and particularly preferably 27% by weight or more and 35% by weight or less. By setting the ratio of the hard segment within this range, the adhesion of the resin layer to the foam substrate, particularly to a foam substrate made of a polyurethane foam or a polyolefin foam, is improved.

[0053] The molecular weight (weight average molecular weight) of the hard segment is preferably 50,000 or more, more preferably 53,000 or more, and even more preferably 55,000 or more. The molecular weight of the hard segment is preferably 100,000 or less, more preferably 75,000 or less, and even more preferably 70,000 or less. When the molecular weight of the hard segment is within this range, it can exhibit particularly excellent reworkability.

[0054] The ratio of the soft segment in the block copolymer is preferably 50% by weight or more and 90% by weight or less, more preferably 55% by weight or more and 88% by weight or less, even more preferably 60% by weight or more and 86% by weight or less, and particularly preferably 65% ​​by weight or less. By setting the ratio of the soft segment within this range, the adhesion of the resin layer to the foam substrate, particularly to a foam substrate made of a polyurethane foam or a polyolefin foam, is improved.

[0055] The molecular weight (weight average molecular weight) of the soft segment is preferably 100,000 or more, more preferably 130,000 or more, and even more preferably 150,000 or more. The molecular weight of the soft segment is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 380,000 or less. When the molecular weight of the soft segment is within this range, the resin layer exhibits high tackiness and improves adhesion to the foam substrate, particularly to a foam substrate made of a polyurethane foam or a polyolefin foam.

[0056] When the resin layer contains the block copolymer, it is preferable that a spherical or cylindrical phase separation structure can be observed when the cross section of the resin layer is observed with an atomic force microscope (AFM). The observation of such a spherical or cylindrical phase separation structure means that the resin layer has a microphase separation structure. The spherical shape means that the microphase separation structure is a spherical structure, and the cylindrical shape means that the microphase separation structure is a cylindrical structure. This allows the resin layer to have both flexibility and strength, and to exhibit excellent resistance to tilting load and reworkability. Although the above-mentioned spherical or cylindrical phase separation structure may be observed in both the first resin layer and the second resin layer, it is sufficient that the above-mentioned spherical or cylindrical phase separation structure is observed in at least one selected from the group consisting of the first resin layer and the second resin layer.

[0057] Examples of the block copolymer include styrene-based block copolymers, acrylic-based block copolymers, styrene-acrylic-based block copolymers, polyetherester-based block copolymers, urethane-based block copolymers, vinyl chloride-based block copolymers, amide-based block copolymers, etc. Among these, styrene-acrylic-based block copolymers are preferred because they allow easy adjustment of the tensile modulus and breaking stress of the resin layer and also exhibit sufficient tackiness to facilitate lamination onto the foam substrate.

[0058] The styrene-acrylic block copolymer is a block copolymer of styrene and an alkyl (meth)acrylate. The styrene-acrylic block copolymer has a block derived from styrene and a block derived from an alkyl (meth)acrylate. Usually, in the styrene-acrylic block copolymer, the block derived from styrene constitutes a hard segment, and the block derived from an alkyl (meth)acrylate constitutes a soft segment. That is, a styrene-acrylic block copolymer containing a block derived from styrene as a component constituting a hard segment and a block derived from an alkyl (meth)acrylate as a component constituting a soft segment is preferable.

[0059] The styrene-acrylic block copolymer contains styrene as a component constituting the hard segment, which makes it possible to easily adjust the tensile modulus and breaking stress of the resin layer. The proportion of styrene in the entire styrene-acrylic block copolymer is preferably 10% by weight or more, more preferably 12% by weight or more, even more preferably 15% by weight or more, and particularly preferably 20% by weight or more, from the viewpoint of further increasing the resistance to tilting load. The proportion of styrene in the entire styrene-acrylic block copolymer is preferably 50% by weight or less, more preferably 45% by weight or less, and even more preferably 40% by weight or less, from the viewpoint of further increasing the adhesion between the resin layer and the foam substrate. The proportion of styrene in the hard segment of the styrene-acrylic block copolymer is preferably 70% by weight or more, and more preferably 80% by weight or more.

[0060] The styrene-acrylic block copolymer may contain a component other than styrene as a component constituting the hard segment. Examples of the components other than styrene include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and polypropylene glycol mono(meth)acrylate. Also, for example, (meth)acrylic acid esters having a hydroxyl group, such as 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate, can be used. For example, monomers having a carboxyl group, such as (meth)acrylic acid, can be used. For example, monomers having a glycidyl group, such as glycidyl (meth)acrylate, can be used. For example, monomers having an amide group, such as hydroxyethyl (meth)acrylamide, isopropyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide, can be used. Monomers having a nitrile group, such as (meth)acrylonitrile, can be used. Furthermore, various monomers used in general (meth)acrylic copolymers, such as vinyl carboxylates, such as vinyl acetate, acrylonitrile, and styrene, can also be used.

[0061] As the component other than styrene, it is preferable to contain a monomer having at least one selected from the group consisting of a carboxyl group and a hydroxyl group. By containing a monomer having at least one selected from the group consisting of a carboxyl group and a hydroxyl group as a component constituting a hard segment, the styrene-acrylic block copolymer can be crosslinked with a crosslinking agent. This makes it possible to form the resin layer by, for example, applying the styrene-acrylic block copolymer before crosslinking onto the foam substrate and then crosslinking it, thereby improving manufacturability. When a monomer having a carboxyl group is contained as a component other than the styrene, the ratio of the monomer having a carboxyl group in the hard segment is preferably 10% by weight or more. The crosslinking agent is not particularly limited, and a general one such as an isocyanate-based crosslinking agent can be used.

[0062] The monomer having at least one selected from the group consisting of a carboxyl group and a hydroxyl group may be contained in the soft segment of the styrene-acrylic block copolymer. That is, the styrene-acrylic block copolymer preferably has at least one selected from the group consisting of a carboxyl group and a hydroxyl group in at least one selected from the group consisting of a hard segment and a soft segment. This makes it possible for the styrene-acrylic block copolymer to be crosslinked with a crosslinking agent. For example, the resin layer can be formed by applying the styrene-acrylic block copolymer before crosslinking onto the foam substrate and then crosslinking the copolymer, thereby improving manufacturability.

[0063] The component other than the styrene may contain a (meth)acrylic acid ester having a hydroxyl group. By including a (meth)acrylic acid ester having a hydroxyl group as a component constituting a hard segment, the adhesion between the resin layer and the foam base material can be improved. When a (meth)acrylic ester having a hydroxyl group is contained as a component other than the styrene, the proportion of the (meth)acrylic ester having a hydroxyl group in the hard segment is preferably 0.1% by weight or more.

[0064] The styrene-acrylic block copolymer contains a (meth)acrylic acid alkyl ester as a component constituting the soft segment, which makes it possible to easily adjust the tensile modulus and breaking stress of the resin layer.

[0065] Examples of the (meth)acrylic acid alkyl ester include the various (meth)acrylic acid alkyl esters described as components other than styrene constituting the hard segment. Among them, n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate is preferred because it can impart high tackiness to the resin layer. The ratio of the component derived from n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate in the soft segment of the styrene-acrylic block copolymer is preferably 10% by weight or more, more preferably 20% by weight or more, even more preferably 30% by weight or more, particularly preferably 40% by weight or more, and may be 100% by weight.

[0066] The (meth)acrylic acid alkyl ester preferably further contains methyl (meth)acrylate or ethyl (meth)acrylate, and more preferably contains methyl (meth)acrylate, since this makes it easy to adjust the tensile modulus and breaking stress of the resin layer. The ratio of the component derived from methyl (meth)acrylate in the soft segment of the styrene-acrylic block copolymer is preferably 45% by weight or more, more preferably 47% by weight or more, even more preferably 50% by weight or more, and particularly preferably 53% by weight or more. The ratio is preferably 80% by weight or less, more preferably 70% by weight or less, and even more preferably 60% by weight or less.

[0067] The weight average molecular weight of the block copolymer is not particularly limited, but from the viewpoint of further improving the resistance to tilting load, it is preferably 120,000 or more and 450,000 or less, more preferably 150,000 or more and 400,000 or less, even more preferably 200,000 or more and 350,000 or less, and even more preferably 220,000 or more and 330,000 or less.

[0068] The resin layer may be colored. By coloring the resin layer, it is possible to impart light-shielding properties to the double-sided pressure-sensitive adhesive tape. The method for coloring the resin layer is not particularly limited, and examples thereof include a method of kneading particles of carbon black, titanium oxide, or the like, or fine air bubbles into the resin constituting the resin layer, and a method of applying ink to the surface of the resin layer.

[0069] The resin layer may contain, as necessary, conventionally known fine particles and additives such as inorganic fine particles, conductive fine particles, plasticizers, tackifiers, ultraviolet absorbers, antioxidants, foaming agents, organic fillers, inorganic fillers, etc. In addition, when at least one selected from the group consisting of the first resin layer and the second resin layer contains a thermoplastic elastomer, the resin may contain a resin other than the thermoplastic elastomer.

[0070] The gel fraction of the resin layer is not particularly limited, but from the viewpoint of further enhancing the adhesion between the resin layer and the foam substrate, it is preferably 10% by weight or more and 90% by weight or less, more preferably 20% by weight or more and 85% by weight or less, and even more preferably 30% by weight or more and 80% by weight or less. The gel fraction of the resin layer can be measured in the same manner as the gel fraction of the adhesive layer by preparing a double-sided adhesive tape having a resin layer but no adhesive layer for the purpose of gel fraction measurement.

[0071] The thickness of the resin layer is not particularly limited, but the preferred lower limit is 5 μm, and the preferred upper limit is 100 μm. By setting the thickness of the resin layer within this range, the double-sided pressure-sensitive adhesive tape of the present invention can exhibit better reworkability. From the viewpoint of further improving reworkability, the more preferred lower limit of the thickness of the resin layer is 10 μm, and the more preferred upper limit is 70 μm.

[0072] The double-sided pressure-sensitive adhesive tape of the present invention may, if necessary, have layers other than the foam substrate, the pressure-sensitive adhesive layer, and the resin layer.

[0073] The thickness of the double-sided adhesive tape of the present invention is not particularly limited, but the preferred lower limit is 200 μm, and the preferred upper limit is 2000 μm. If the thickness is 200 μm or more, the adhesive strength of the double-sided adhesive tape is sufficient, and the stress relaxation property is also sufficient. If the thickness is 2000 μm or less, sufficient adhesion and fixation by the double-sided adhesive tape can be realized. The more preferred lower limit of the thickness is 250 μm, and the more preferred upper limit is 1600 μm, and the even more preferred lower limit is 350 μm, and the even more preferred upper limit is 1500 μm, and the even more preferred lower limit is 400 μm, and the even more preferred upper limit is 1300 μm.

[0074] The double-sided pressure-sensitive adhesive tape of the present invention can be produced, for example, by the following method: First, a laminate of the foam substrate and the first resin layer is produced, and then a second resin layer is laminated on this laminate to form a laminate consisting of the first resin layer / foam substrate / second resin layer. Here, when the styrene-acrylic block copolymer is used as the resin constituting the resin layer, the resin layer has tackiness, so that the resin layer and the foam substrate can be easily laminated. In addition, the adhesion can be improved by pressing the resin layer and the foam substrate with a heated laminator. In addition, the adhesion can be improved by inserting the resin layer during the process of foaming the substrate raw material to obtain the foam substrate. In addition, the adhesion between the resin layer and the foam substrate can be improved by performing a surface treatment (for example, plasma treatment or corona treatment) on the surface of the resin sheet used as the resin layer or the foam substrate. Furthermore, when the resin layer does not have self-adhesiveness, an adhesive layer may be provided between the foam substrate and the resin layer and laminated. The adhesion between the resin layer and the foam substrate can also be improved by modifying the polymer chain of the resin layer with a hydroxyl group or an acid group that serves as a reaction site.

[0075] Next, a pressure-sensitive adhesive solution for forming the pressure-sensitive adhesive layer is prepared, the pressure-sensitive adhesive solution is applied to the release-treated surface of the release film, and the solvent in the solution is completely dried and removed to form a first pressure-sensitive adhesive layer. This first pressure-sensitive adhesive layer is laminated on the surface of the first resin layer side of the laminate consisting of the first resin layer / foam substrate / second resin layer in a state where the first pressure-sensitive adhesive layer faces the first resin layer side. On the other hand, a release film other than the above release film is prepared, and a pressure-sensitive adhesive solution is applied to the release-treated surface of this release film, and the solvent in the solution is completely dried and removed to produce a laminate film in which a second pressure-sensitive adhesive layer is formed on the surface of the release film. The obtained laminate film is superimposed on the surface of the second resin layer side of the laminate consisting of the above first resin layer / foam substrate / second resin layer in a state in which the second pressure-sensitive adhesive layer faces the second resin layer side to obtain a laminate consisting of the first pressure-sensitive adhesive layer / first resin layer / foam substrate / second resin layer / second pressure-sensitive adhesive layer. Then, by pressing the obtained laminate with a rubber roller or the like, a double-sided pressure-sensitive adhesive tape having the first pressure-sensitive adhesive layer / first resin layer / foam substrate / second resin layer / second pressure-sensitive adhesive layer and the surfaces of both pressure-sensitive adhesive layers covered with a release film can be obtained. In addition, when winding up the roll, the release film in contact with the second pressure-sensitive adhesive layer is peeled off, and the second pressure-sensitive adhesive layer can be wound up on the inside. In this case, it is necessary that the release film in contact with the first pressure-sensitive adhesive layer has been subjected to release treatment on both sides.

[0076] The applications of the double-sided pressure-sensitive adhesive tape of the present invention are not particularly limited, and it is used, for example, in display devices such as televisions, monitors, etc. The shape of the double-sided pressure-sensitive adhesive tape of the present invention for these applications is not particularly limited, and examples thereof include a rectangular shape, a frame shape, a circular shape, an oval shape, a doughnut shape, etc. Since the double-sided pressure-sensitive adhesive tape of the present invention can be easily wound into a roll while suppressing the occurrence of wrinkles and folds, it is usually stored in a rolled state and can be used by being unwound from the roll.

[0077] Examples of articles for which the double-sided pressure-sensitive adhesive tape of the present invention can be used include flat panel displays used in TVs, monitors, portable electronic devices, etc., camera modules for portable electronic devices, internal components for portable electronic devices, interiors for vehicles, and the interior and exterior of home appliances (e.g., TVs, air conditioners, refrigerators, etc.). Examples of substrates for the double-sided pressure-sensitive adhesive tape of the present invention include side panels, back panels, various nameplates, decorative films, ornamental films, etc. for portable electronic devices. Effect of the Invention

[0078] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive tape that has excellent resistance to tilted loads and excellent reworkability on both adhesive surfaces. [Brief description of the drawings]

[0079] [Figure 1] 1 is a cross-sectional view illustrating a schematic example of a double-sided pressure-sensitive adhesive tape of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a method for measuring shear breaking strength. [Diagram 3] FIG. 2 is a schematic diagram showing a holding power test of a double-sided adhesive tape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0081] (Manufacture of Chain Transfer Agents (RAFT Agents)) 0.902 g of 1,6-hexanedithiol, 1.83 g of carbon disulfide, and 11 mL of dimethylformamide were added to a two-neck flask and stirred at 25 ° C. 2.49 g of triethylamine was added dropwise over 15 minutes and stirred at 25 ° C for 3 hours. Next, 2.75 g of methyl-α-bromophenylacetic acid was added dropwise over 15 minutes and stirred at 25 ° C for 4 hours. After that, 100 mL of extraction solvent (n-hexane: ethyl acetate = 50: 50) and 50 mL of water were added to the reaction liquid for liquid separation and extraction. The organic layers obtained in the first and second liquid separation extractions were mixed and washed with 50 mL of 1 M hydrochloric acid, 50 mL of water, and 50 mL of saturated saline in that order. Sodium sulfate was added to the organic layer after washing and dried, and then the sodium sulfate was filtered, and the filtrate was concentrated with an evaporator to remove the organic solvent. The obtained concentrate was purified by silica gel column chromatography to obtain a RAFT agent.

[0082] (Preparation of styrene-acrylic block copolymer A) 87g of styrene (St), 1g of 2-hydroxyethyl acrylate (HEA), 12g of acrylic acid (AAc), 1.6g of RAFT agent, and 0.35g of 2,2'-azobis(2-methylbutyronitrile) (ABN-E) were added to a reactor, and the temperature was raised to 85°C while replacing the inside of the reactor with nitrogen gas. After that, the polymerization reaction was carried out by stirring at 85°C for 6 hours (first stage reaction). After the first-stage reaction was completed, 4,000 g of n-hexane was added to the flask and stirred to precipitate the reaction product. The unreacted monomers (St, HEA, AAc) and RAFT agent were then filtered off, and the reaction product was dried under reduced pressure at 70°C to obtain a copolymer (hard segment A). A mixture (soft segment B) consisting of 25 g of butyl acrylate (BA), 75 g of methyl acrylate (MA), 0.035 g of ABN-E, and 50 g of ethyl acetate and the copolymer obtained above (hard segment A) were placed in a two-neck flask, and the temperature was raised to 85°C while replacing the atmosphere in the flask with nitrogen gas. After that, the mixture was stirred at 85°C for 6 hours to carry out a polymerization reaction, and a reaction liquid containing a styrene-acrylic block copolymer A consisting of hard segment A and soft segment B was obtained. The blending amounts of the mixture (soft segment B) and the hard segment A were set so that the mass ratio of the hard segment to the soft segment in the resulting block copolymer was 24 / 76. The composition of the resulting styrene-acrylic block copolymer A is shown in Table 1.

[0083] (Preparation of styrene-acrylic block copolymers B to H) Except for changing the composition to that shown in Table 1, reaction solutions containing styrene-acrylic block copolymers B to H were obtained in the same manner as for styrene-acrylic block copolymer A.

[0084] [Table 1]

[0085] (Production of polyethylene (PE) foam substrate) As a polyolefin resin, low-density polyethylene (UBE Polyethylene F420 manufactured by Ube Maruzen Polyethylene Co., Ltd., density 0.920 g / cm 3 100 parts by weight of this polyethylene resin, 8 parts by weight of azodicarbonamide as a thermal decomposition type foaming agent, 1 part by weight of zinc oxide as a decomposition temperature regulator, and 0.5 parts by weight of 2,6-di-t-butyl-p-cresol as an antioxidant were fed to an extruder and melt-kneaded at 130°C, and a long sheet-like foam raw material having a thickness of about 0.2 mm was extruded. Next, both sides of the long sheet-like foam raw material were crosslinked by irradiating 4.0 Mrad of electron beams with an acceleration voltage of 500 kV. The crosslinked foam raw material was continuously sent into a foaming furnace maintained at 250 ° C. by hot air and infrared heaters to be heated and foamed, and stretched at MD stretch ratios of 2.5 times and TD stretch ratios of 2.5 times while foaming. As a result, a polyethylene resin foam having the physical properties shown in Table 2 or 3 was obtained. In Example 7, the thickness of the polyethylene resin foam was adjusted by adjusting the stretch ratio. In Example 8, the density of the polyethylene resin foam was adjusted by adjusting the expansion ratio, and the shear breaking strength was adjusted.

[0086] (Production of polyurethane (PU1) foam substrate) As the polyol, a polyester polyol (polyol component / acid component blend ratio (weight ratio) = 8:1) consisting of 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 800) and 10 parts by weight of neopentyl glycol as the polyol component and ε-caprolactam as the acid component was used. To a total of 100 parts by weight of polyol, 0.7 parts by weight of an amine catalyst (DABCO LV33, manufactured by Sankyo Air Products Co., Ltd.) and 1 part by weight of a foam stabilizer (SZ5740M, manufactured by Dow Corning Toray Co., Ltd.) were added and stirred. Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 80 or 70. Then, 0.2 g / cm 3 The mixture was mixed with nitrogen gas and stirred until the mixture became uniform, giving a solution containing fine bubbles. The solution was applied to a predetermined thickness on a 50 μm-thick PET separator (Nippa Corporation, V-2) using an applicator, and the foam raw material was reacted to give a polyurethane resin foam (PU1 foam base material) having the physical properties shown in Tables 2 and 3. In Example 2, the isocyanate index was set to 80, and in Comparative Examples 4, 5, and 7, the isocyanate index was set to 70, and the density of the polyurethane resin foam was adjusted to adjust the shear breaking strength.

[0087] (Production of polyurethane (PU2) foam substrate) As the polyol, polypropylene glycol (PPG), neopentylin glycol, and adipic acid were used (polyether component / polyester component blending ratio (weight ratio)=2:1). To a total of 100 parts by weight of polyol, 0.7 parts by weight of an amine catalyst (DABCO LV33, manufactured by Sankyo Air Products Co., Ltd.) and 1 part by weight of a foam stabilizer (SZ5740M, manufactured by Dow Corning Toray Co., Ltd.) were added and stirred. Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 90. Then, 0.2 g / cm 3The mixture was mixed with nitrogen gas and stirred until the mixture became uniform, giving a solution with fine bubbles mixed in. The solution was applied to a specified thickness on a 50 μm-thick PET separator (Nippa Corporation, V-2) using an applicator, and the foam raw material was reacted to give a polyurethane resin foam (PU2 foam base material) having the physical properties shown in Table 3.

[0088] (Preparation of Adhesive Solution A) 52 parts by weight of ethyl acetate was put into a reactor equipped with a thermometer, a stirrer, and a cooling tube, and after replacing with nitrogen, the reactor was heated to start reflux. 30 minutes after the ethyl acetate boiled, 0.08 parts by weight of azobisisobutyronitrile was added as a polymerization initiator. A monomer mixture consisting of 47.5 parts by weight of butyl acrylate, 47.5 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate was added dropwise evenly and gradually over 1 hour and 30 minutes to react. 30 minutes after the end of the dropwise addition, 0.1 parts by weight of azobisisobutyronitrile was added, and the polymerization reaction was continued for another 5 hours. Ethyl acetate was added to the reactor to dilute it and cool it, obtaining a solution of an acrylic copolymer with a solid content of 25% by weight. The weight average molecular weight of the obtained acrylic copolymer was measured by GPC using a Waters "2690 Separations Model" column, and was found to be 710,000. The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) was 2.7. To 100 parts by weight of the solid content of the obtained acrylic copolymer, 12 parts by weight of polymerized rosin ester having a softening point of 150° C., 10 parts by weight of terpene phenol having a softening point of 145° C., and 10 parts by weight of rosin ester having a softening point of 70° C. were added. Furthermore, 30 parts by weight of ethyl acetate (manufactured by Fuji Chemicals Co., Ltd.) and 3.0 parts by weight of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L45") were added and stirred to obtain a pressure-sensitive adhesive solution.

[0089] (Preparation of Adhesive Solution B) 52 parts by weight of ethyl acetate was put into a reactor equipped with a thermometer, a stirrer, and a cooling tube, and after replacing with nitrogen, the reactor was heated to start reflux. 30 minutes after the ethyl acetate boiled, 0.08 parts by weight of azobisisobutyronitrile was added as a polymerization initiator. A monomer mixture consisting of 60 parts by weight of butyl acrylate, 36.9 parts by weight of 2-ethylhexyl acrylate, 3 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate was added dropwise evenly and gradually over 1 hour and 30 minutes to react. 30 minutes after the dropwise addition, 0.1 parts by weight of azobisisobutyronitrile was added, and the polymerization reaction was continued for another 5 hours, and ethyl acetate was added to the reactor to dilute it while cooling, to obtain a solution of an acrylic copolymer. The molecular weight distribution (Mw / Mn) of the acrylic copolymer determined in the same manner as above was 6.5. Ethyl acetate was added to 100 parts by weight of the solid content of the obtained acrylic copolymer and stirred, and a total of 30 parts by weight of tackifier resin was added and stirred to obtain an adhesive solution with a non-volatile content of 30% by weight. The tackifier resins used were 10 parts by weight of hydrogenated rosin resin, 10 parts by weight of rosin ester resin, and 10 parts by weight of terpene phenol resin.

[0090] Example 1 (1) Preparation of First and Second Resin Layers As the first and second resin layers, polyethylene terephthalate (PET) sheets (manufactured by Toray Industries, Inc., X30) having a thickness of 50 μm and the physical properties shown in Table 2 were prepared.

[0091] (2) Manufacturing of double-sided adhesive tapes The adhesive solution A was applied to the surface of the first resin layer and dried for 5 minutes at 100° C. to form an adhesive layer having a thickness of 20 μm. A PE foam substrate was laminated on the adhesive layer to obtain a laminate consisting of the first resin layer (adhesive layer) / foam substrate. Furthermore, a 20 μm-thick adhesive layer was formed by applying the above-mentioned adhesive solution A to the surface of the second resin layer and drying it for 5 minutes at 100° C. The foam substrate side of a laminate consisting of a first resin layer (adhesive layer) / foam substrate was laminated on the adhesive layer to obtain a laminate consisting of a first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer).

[0092] The above adhesive solution A was applied to the release-treated surface of a release liner consisting of polyethylene (PE) / high-quality paper / polyethylene (PE) with a thickness of 100 μm and dried at 100° C. for 5 minutes to form a first adhesive layer with a thickness of 50 μm. The above adhesive solution A was applied to the release-treated surface of a release liner consisting of polyethylene (PE) / high-quality paper / polyethylene (PE) with a thickness of 100 μm and dried at 100° C. for 5 minutes to form a second adhesive layer with a thickness of 50 μm.

[0093] The release liner on which the first adhesive layer was formed was superposed on the surface of the first resin layer side of the laminate consisting of the first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer) in a state in which the first adhesive layer faced the first resin layer side. This resulted in a laminate consisting of the first adhesive layer / first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer). The release liner on which the second adhesive layer was formed was superposed on the surface of the second resin layer side of the laminate consisting of the first adhesive layer / first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer) in a state in which the second adhesive layer faced the second resin layer side. This resulted in a laminate consisting of the first adhesive layer / first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer) / second adhesive layer. Then, the obtained laminate was pressed with a rubber roller to obtain a double-sided adhesive tape having a first adhesive layer / first resin layer (adhesive layer) / foam substrate / second resin layer (adhesive layer) / second adhesive layer, with the surface of each adhesive layer covered with a release liner.

[0094] (Examples 2 to 15, Comparative Examples 1 to 10) A double-sided pressure-sensitive adhesive tape was obtained in the same manner as in Example 1, except that the first and second resin layers and the foam substrate were changed as shown in Table 2 or 3.

[0095] When a styrene-acrylic block copolymer was used in place of a polyethylene terephthalate (PET) sheet for the first or second resin layer, the following procedure was carried out. (Preparation of the second resin layer) For the second resin layer, 5 parts by weight of a crosslinking agent was mixed with 100 parts by weight of the styrene-acrylic block copolymer in an ethyl acetate solution of the styrene-acrylic block copolymer, and the mixture was applied to a 50 μm-thick polyethylene terephthalate (PET) sheet with a release treatment on the surface, and then dried to obtain a 50 μm-thick uncrosslinked resin film. The crosslinking agent used was "Coronate L45" manufactured by Nippon Polyurethane Co., Ltd. An uncrosslinked resin film was laminated on the foam substrate side of the obtained laminate consisting of the first resin layer (adhesive layer) / foam substrate to form a laminate consisting of the first resin layer (adhesive layer) / foam substrate / uncrosslinked resin film. Next, by heating at 40°C for 48 hours to cause thermal crosslinking, a laminate consisting of the first resin layer (adhesive layer) / foam substrate / second resin layer was obtained with the uncrosslinked resin film as the second resin layer. Regarding the physical properties of the second resin layer, the uncrosslinked resin film was heated at 40°C for 48 hours to cause thermal crosslinking to obtain a second resin layer measurement sample having a thickness of 50 μm, and the physical properties were measured.

[0096] In Comparative Example 1, LA2140 manufactured by Kuraray Co., Ltd. and having the physical properties shown in Table 3 was used for the first and second resin layers, and in Comparative Example 7, LA2270 manufactured by Kuraray Co., Ltd. and having the physical properties shown in Table 3 was used for the second resin layer.

[0097] <Evaluation> The double-sided pressure-sensitive adhesive tapes obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 2 and 3.

[0098] (1) 20° tilt holding test FIG. 3 shows a schematic diagram of a holding power test of a double-sided adhesive tape. First, one side (front side) of a test piece 18 of a double-sided adhesive tape with a size of 25 mm×25 mm was attached to a glass plate 17, and a 2 kg rubber roller was reciprocated from the other side (back side) of the test piece 18 at a speed of 300 mm / min. Next, an aluminum plate 16 was attached to the back side of the test piece 18, and a 5 kg weight was applied from the aluminum plate 16 side for 10 seconds to be pressed and bonded, and then the aluminum plate 16 was left in an environment of 23° C. and 50% relative humidity for 24 hours to prepare a holding power test sample. The holding power test sample was held at 80° C. and 90% relative humidity, and a 1.5 kg weight 15 was attached to the center of the aluminum plate 16 so that a load was applied horizontally to the test piece 18 and the aluminum plate 16, and the weight 15 was held in a tilted state of 20°, and the time until the weight 15 fell (fall time) was measured. ◎: Fall time is more than 200 hours 〇: Fall time is more than 15 hours but less than 200 hours ×: Fall time is less than 15 hours

[0099] (2) Reworkability evaluation The obtained double-sided adhesive tape was cut into a size of 5 mm wide x 100 mm long to prepare a sample. The release liner on the first adhesive layer side of the obtained sample was peeled off, and the first adhesive layer side was attached to a glass plate (50 mm wide, 125 mm long) having a thickness of 2 mm. A 2 kg rubber roller was run back and forth on the double-sided adhesive tape at a speed of 300 mm / min, and then the double-sided adhesive tape was left for 24 hours under an environment of 23°C and 50% relative humidity. Next, the interlayer of the foam substrate was torn up, and the second adhesive layer, the second resin layer, and a part of the foam substrate were removed from the double-sided adhesive tape. The remaining part of the double-sided adhesive tape was pulled at an angle of 30° from the horizontal direction at a speed of 300 mm / min, and the remaining part of the double-sided adhesive tape was peeled off from the glass plate. The reworkability of the first adhesive layer side was evaluated according to the following criteria. The second adhesive layer side was also evaluated in the same manner. ○: The remaining part of the double-sided adhesive tape could be removed. △: Part of the double-sided adhesive tape broke during peeling, but it could be removed. ×: The remaining part of the double-sided adhesive tape could not be removed.

[0100] (3) Evaluation of roll winding properties The obtained double-sided adhesive tape (release liner / first adhesive layer / first resin layer / foam substrate / second resin layer / second adhesive layer / release liner) was wound around a 3-inch diameter paper core with the second adhesive layer side facing inward to obtain a roll-like body. The side and surface layers of the obtained roll-shaped product were visually observed, and then the double-sided pressure-sensitive adhesive tape was pulled out from the roll-shaped product, and the tape was visually observed from the second pressure-sensitive adhesive layer side and evaluated according to the following criteria. ○: No wrinkles or creases were observed in any of the areas examined. △: Wrinkles and creases were observed in some areas. ×: Wrinkles and folds were found in all observed locations.

[0101] [Table 2]

[0102] [Table 3] [Industrial Applicability]

[0103] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive tape that has excellent resistance to tilted loads and excellent reworkability on both adhesive surfaces. [Explanation of symbols]

[0104] 1 Double-sided adhesive tape 2. Foam substrate 15 Weight (1.5kg) 16 Aluminum plate 17 Glass Plate 18 Test piece (double-sided adhesive tape) 19 SUS board 31 First adhesive layer 32 Second adhesive layer 41 First resin layer 42 Second resin layer

Claims

1. A double-sided pressure-sensitive adhesive tape having a foam substrate and a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer on both sides of the foam substrate, The foam base material has a shear breaking strength of 200 N / inch. 2 That's all. a first resin layer and a second resin layer, each having a tensile modulus of elasticity of 5.0 MPa or more, are provided between the foam substrate and the first pressure-sensitive adhesive layer, and between the foam substrate and the second pressure-sensitive adhesive layer, At least one selected from the group consisting of the first resin layer and the second resin layer contains a thermoplastic elastomer, The thermoplastic elastomer contains a block copolymer, the block copolymer is a styrene-acrylic block copolymer, The styrene-acrylic block copolymer contains a component derived from methyl (meth)acrylate. A double-sided adhesive tape characterized by:

2. The double-sided adhesive tape according to claim 1, characterized in that the first resin layer and the second resin layer have a breaking stress of 6 MPa or more and less than 50 MPa and a breaking elongation of 300% or more, or a breaking stress of 50 MPa or more and a breaking elongation of 110% or more.

3. 3. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate is a polyolefin foam.

4. 4. The double-sided tape according to claim 1, wherein at least one selected from the group consisting of the first resin layer and the second resin layer has a tensile modulus of elasticity of 150 MPa or less.

5. 5. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the difference in tensile modulus between the first resin layer and the second resin layer is 20 MPa or more.

6. A double-sided adhesive tape as described in claim 1, 2, 3, 4 or 5, characterized in that the triblock ratio in the block copolymer is 50 weight % or more.

7. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5 or 6, characterized in that the proportion of styrene in the entire styrene-acrylic block copolymer is 10% by weight or more.

8. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6 or 7, characterized in that at least one selected from the group consisting of the first resin layer and the second resin layer has a spherical or cylindrical phase separation structure when the cross section is observed with an atomic force microscope (AFM).

9. 9. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the styrene-acrylic block copolymer has a content of a component derived from methyl (meth)acrylate in the soft segment of 45% by weight or more.

10. 10. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the block copolymer has a hard segment ratio of 22% by weight or more.

11. 11. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the block copolymer has a weight average molecular weight of 120,000 or more and 450,000 or less.

12. The double-sided pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11, characterized in that the styrene-acrylic block copolymer has at least one selected from the group consisting of a carboxyl group and a hydroxyl group in at least one selected from the group consisting of a hard segment and a soft segment.

13. 13. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the first resin layer and the second resin layer have a gel fraction of 30% by weight or more.

14. at least one selected from the group consisting of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer contains an acrylic copolymer and a tackifier resin; the acrylic copolymer has a constitutional unit derived from a hydroxyl group-containing monomer, a weight average molecular weight of 300,000 or more and 2,000,000 or less, and a molecular weight distribution (Mw / Mn) of 1.05 or more and 5.0 or less; At least one selected from the group consisting of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer has a gel fraction of 1% by weight or more and 80% by weight or less.

14. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13.

15. 15. The double-sided adhesive tape according to claim 14, wherein the tackifier resin is a rosin-based resin or terpene-based resin containing a hydroxyl group, has a softening temperature of 70°C or higher and 170°C or lower, and a hydroxyl value of 25 or higher and 55 or lower.

16. 16. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has a thickness of 100 μm or more and 1500 μm or less.

17. 17. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16, wherein the double-sided adhesive tape has a thickness of 200 μm or more and 2000 μm or less.

Citation Information

Patent Citations

  • Impact-absorbing tape

    JP2009242541A

  • Pressure-sensitive adhesive sheet for front plate of display device

    JP2009258274A

  • Foam substrate adhesive tape, article and electronic device

    JP2019065213A

  • Double-sided adhesive tape

    JP2020012106A

  • Double-sided adhesive tape

    WO2018181336A1